Penerapan Konsep Higher Order Thinking Skill (HOTs) Pada Soal Penilaian Akhir Semester di Kelas IV MI Ma’arif 1 Jatisari - Dinar Syahputri; Nurhidayah Nurhidayah; Nadia Raifah Nawa Kartika (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to describe the application the concept of Higher Order Thinking Skill(HOTS) in the final assessment of the thematic learning semester even grade IV MI Ma'arif 1Jatisari Academic Year 2021/2022. This approach uses a qualitative, the research design isdescriptive type of document analysis by analysis the final assesment of the thematic learningsemester even grade IV theme 6,7,8, and 9. Data collecting techniques used in the study areobservations, interviews, and documentation studies, while Data analysis techniques usedinclude data reduction, data presentation, and drawing conclusions. The result showed thatthe HOTS assesment category in theme 6 was 7,5%, theme 7 was 17,5%, theme 8 and 9 wasonly 5%, the four assesment had been made with various types of question, based onproblems or contextual situations, as for questions with multirepresentation of theme 6 is7,5%, theme 7 is 10%, theme 8 is 5%, and theme 9 is 22,5%, while the HOTS assesment aredivergent, theme 6 is 15%, theme 7 is 10%, theme 8 is 5%, and theme 9 as much as 22,5%